Factors Influencing Grade 11 Students’ Decision to Study World History as a Subject at Specialized School of Astana - Tolegenova, Aizhan (Nazarbayev University Graduate School of Education, 2017)
In Kazakhstan, as students enter Grade 11, they have to choose their major subjects for further studies, because their admission to university and future career depends on the subjects they choose. This is not an easy decision for students to make as they usually grapple with more than one choice of subjects and their decisions are influenced by many factors. This study explores the factors influencing grade 11 students’ decision to study World History as their major subject at a specialized school in Kazakhstan. The school follows International Baccalaureate (IB) curriculum. The purpose of the study was to study how teachers and students perceive World History subject; what factors motivate students to choose World History; and what factors discourage students to study World History. Using qualitative research methods, data for the study was collected by semi structured one-on-one interviews with students who chose World History subject, teachers who teach World History, parents of 11 grade students and a member from the school leadership. Focus group interview was also conducted with teachers from different subject areas. The finding of the study revealed a number of factors influencing students’ choices of World History subject. These include students’ own personal interests in knowing about the world, their career choice and aspirations, effect of information technology, and scholarship opportunities. The study makes a number of recommendations that might be useful for the school (and other schools) in organizing career counselling programs, parents, and policy makers.
Keywords: secondary school; influence; World History subject; subject choice; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education